Evaluation of the implementation accounting information systems for sales and cash receipts - Manda Yulieta Krisnasari; Novi Khoiriawati (Enrichment : Journal of Management, 2023)
Technology advancements lead to improvements in accounting records. Systems of accounting information are used to assist operational tasks, decision-making, and financial accountability reporting for the organization. The method used in this research is descriptive qualitative research which is used to understand a phenomenon from the research subject by thinking holistically, data collection techniques are carried out through interviews and documentation. Based on the results of the study, first the implementation of the sales accounting information system at UD. Nanda Putri Blitar has been running smoothly since the implementation of records using the purchase journal. Second, the implementation of the cash receipt accounting information system at UD. Nanda Putri Blitar has been running well starting with the application of the accounting information system in the form of credit invoices as proof of cash receipt transactions. Third, evaluate the application of the sales and cash receipts accounting information system at UD. Nanda Putri Blitar, namely related to the company's financial statements which are increasingly detailed due to the application of the accounting information system.